Structure of optimal trajectories in a nonlinear dynamic model with endogenous delay. Issue 5 (18th November 2004) - Hritonenko, Natali; Yatsenko, Yuri
Abstract : An exact solution is constructed to a nonlinear optimization problem in an integral dynamic model with delay. The problem involves the unknown duration of the delay and has important applications to the optimal replacement of capital equipment under technological change.